Modelling the intention to accept Information Technology (IT) innovations among generation-Y / Nor Sahira Miskon - Miskon, Nor Sahira (Faculty of Business and Management, 2012)
This research is carried out to examine the level of Gen-Y intention to accept information technology innovation. The purpose of this research is to identify what is the acceptance factor of information technology innovation among Gen- Y. This study also aims to investigate the relationships between Theory Acceptance Model with the acceptance of Gen-Y towards information technology innovations. This is to find out whether the factors are really contributed to the level of acceptance. To carry out this research a total of 100sets of questionnaire were distributed to the Gen-Y in around Johor Bahru. A total of 100 respondents were identified to complete this study. After findings and analysis, the research results found that there is correlation between TAM with acceptance of information technology innovations among Gen-Y in Johor Bahru.